Biocompatibility of mineral trioxide aggregate and three new endodontic cements: An animal study - Mohammad-Ghasem Aminozarbian; Masoud Barati; Iman Salehi; Seyed Behrouz Mousavi (Wolters Kluwer Medknow Publications, 2012)
Background: Introducing new endodontic cements should await comprehensive investigations and new formulations have to be tested in vivo before applying in human beings. So, the purpose of this study was to compare the biocompatibility of new endodontic cements, calcium aluminate α-aluminate cement (CAAC), calcium aluminate α-aluminate plus cement (CAAC plus), and a mixture of wollastonite and CAAC cement (WOLCA) and mineral trioxide aggregate (MTA), in subcutaneous connective tissue of rats. Materials and Methods: Twenty-seven Wistar rats were divided into three groups of 7, 14, and 30 experimental days. Sterile polyethylene tubes were filled with MTA, CAAC, CAAC Plus, and WOLCA cement and implanted subcutaneously. Empty tubes were implanted as negative control. After the experimental periods, animals were sacrificed by anesthetic overdosing. The occurrence of inflammatory responses was scored according to the previously established scores. Data were statistically analyzed using Friedman, Wilcoxon, Kruskal-Wallis, and Mann-Whitney tests. The level of significance was 5% (P<0.05). Results: There was a statistically significant difference between experimental and negative control sites in each group (P<0.05). CAAC Plus showed the highest mean scores of inflammation, compared with MTA, CAAC, and WOLCA cement sits at the end of all periods (P<0.05). There were no statistically significant differences between inflammatory scores of each site in different experimental groups, except CAAC plus sites, in which inflammation increased significantly with time (P<0.05). Conclusion: According to the results of the current study, biocompatibility of CAAC and WOLCA cement were comparable with that of MTA, but CAAC Plus induced an inflammatory response higher than MTA, therefore is not biocompatible.